SLEEP DURATION: MODERN VIEW OF THE PROBLEM FROM THE STANDPOINT OF A CARDIOLOGIST - O. M. Drapkina; R. N. Shepel' (Столичная издательская компания, 2015)
Today the role of disturbances in sleep duration in the development of various chronic diseases, including cardiovascular diseases is known and proven. In addition, the results of many clinical studies demonstrate the relationship between impaired sleep duration and the rate of telomere shortening. In turn, short telomeres are associated with the development of arterial hypertension, chronic heart failure, atherosclerosis and other diseases with high mortality both in Russia and worldwide. This article presents an overview of the clinical studies demonstrating the negative effect of sleep duration disturbances on total and cardiovascular mortality, as well as works that specify in detail the relation between sleep duration and telomere length.